Flagship report on policy coherence of food, land and water systems in Nigeria - Osei-Amponsah, Charity; Appiah, Sarah; Balana, Bedru; Sanchez Ramirez, Juan Carlos; Nicol, Alan (International Water Management Institute (IWMI). CGIAR Initiative on National Policies and Strategies, 2024)
The Sustainable Development Goals are interconnected and cut across Food, Land and Water (FLW) systems. But the formulation and implementation of national policy objectives to attain the SDGs may be fragmented and uncoordinated. The CGIAR Initiative on National Policies and Strategies (NPS), aims to contribute to agri-foods system transformation, by identifying ways of building stronger FLW policies with greater coherence and investment capacity, to support Nigeria in addressing current crises and future development needs. This flagship report focuses on (in)coherence in policies related to FLW systems in Nigeria, through the lens of Policies and Institutions Landscape Analysis Framework. To achieve policy coherence for sustainable development, the report highlights the need for: 1. strengthening staff and institutional capacities for FLW contextual and policy analysis to effectively identify, anticipate and respond to crisis. 2. developing systemic polycentric decision-making and governance, involving multi-stakeholders at the Federal, State and Local levels. 3. providing sustainable funding for the effective implementation of policy objectives, projects and programmes in the relevant FLW-related sectors 4. maintaining continuity of the implementation of ongoing transformative FLW policy objectives and programmes when an incumbent government comes into power. 5. promoting evidence-based (real time and high-quality data) policy formulation, monitoring, evaluation, and learning.